If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 3 = 52 Reorder the terms: 3 + 2x = 52 Solving 3 + 2x = 52 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 2x = 52 + -3 Combine like terms: 3 + -3 = 0 0 + 2x = 52 + -3 2x = 52 + -3 Combine like terms: 52 + -3 = 49 2x = 49 Divide each side by '2'. x = 24.5 Simplifying x = 24.5
| 3x=x+10+40 | | 2s+3t=27 | | 6x-5=7(x-2) | | 6x-41=25 | | 11x-23=30-8x | | 2+14x-40=11-3x+2x | | (x+3i)(x+3i)=2yi | | 3(2x+1)-4x=2x+3 | | -3=8+4x | | 7x+8y-9=0 | | 3x-6.3=7.5 | | 8(x-5)=4x-4 | | 9+7*2= | | .666x+6=.5x+.25x | | 3x-8=-3x+28 | | 4x-7y+5=0 | | 2x+24=0 | | 3n^2-10n+4=0 | | r=2(3.14)sh | | 9m+(-5m)= | | -6x+16=16 | | 7x^2-45x-343=0 | | 3y-10+y+28=5y+20-3y | | 6x+3x=x+14 | | m=3(1,6) | | 8x^2-59x+40=0 | | 14x^2+7x+14=0 | | 8(w-3)=16 | | |-3|-|2-17|= | | n+n+1+n+2+n+3=s | | 16-(5m+8)=5+2M-11 | | |11-2|-|3-1|= |